PERCEPTION OF BANKS’ STAFF ON COMPETITION AND MARKETING STRATEGIES IN NORTH-EASTERN NIGERIA - Babatunde BELLO, Kamarudeen; Aliyu YAMTA, Hauwa; Modu KUMSHE, Hauwa (British Journal of Marketing Studies, 2014)
The study focuses on the perceptions of banks’ staff with regards to competition in the Nigerian banking industry and the marketing strategies that the banks have employed to cope with the competition. The primary data for the study were obtained using a structured questionnaire administered on a sample of 100 staff of selected banks in Jimeta-Yola, the capital city of Adamawa state, North-eastern Nigeria. The data obtained from the questionnaire were analysed using percentages, mean, and the Pearson correlation analysis. The findings revealed that the top-5 factors influencing competition are the reputation or rating of banks, overall strategy adopted by the banks, effective deployment of ICT and associated facilities, incentives that individual banks give to their marketers and regulations/reforms by the government. Personal selling, relationship marketing and new product development were also found to be the dominant strategies employed by the bank as they significantly impact on customer and deposit attraction, new product adoption as well as marketing costs.